Implementasi Metode STIFIN dalam Meningkatkan Karakter Islami Peserta Didik di Sekolah Alam - Abdul Halim Sholeh; Arina Alfa Khasanatin; Syahidah Rena (Idrak: Journal of Islamic Education, 2022)
Each student has a different type of intelligence and potential.One way to find out the personality of students is the STIFIn method, which is a method that describes the type of intelligence or personality of a person based on the dominant hemisphere of the brain.The purpose of this study was to determine the implementation of the STIFIn method in improving the Islamic character of students at SD Islam Ibnu Hajar Bogor. This research uses descriptive qualitative research. The STIFIn method in improving the character of students can be a tool in identifying children's character and determining indicators of child character achievement according to their intelligence machine, as well as assisting teachers in identifying problems in children and solutions to overcome them. Character enhancement applied at the Islamic Elementary School of Ibnu Hajar is distinguished according to its level, for level 1-2 character enhancement is independent, for level 3-4 is confident and level 5-6 is I'm brave, Meanwhile in improving the Islamic character that is applied at the Ibnu Hajar Islamic Elementary School Bogor it is carried out through example and habituation to religious programs in order to achieve the school's mission namely to become a generation of Rahmatan lil' Alamin.